Comparative efficacy and safety of induction therapy in solid organ transplantation: a systematic review and network meta-analysis - Sun, Junjie; Hu, Chao; Liang, Qingwen; Yu, Yanqing; Wen, Ning; Dong, Jianhui; Li, Haibin; Sun, Xuyong (Frontiers in Immunology, 2025)
ObjectiveTo comparatively evaluate the efficacy and safety of induction therapies in solid organ transplantation (SOT) using a Bayesian network meta-analysis (NMA).MethodsRandomized controlled trials (RCTs) assessing induction therapies were systematically identified across major databases (up to November 20, 2024). The screening, data extraction, and risk of bias (ROB) assessment were independently conducted by two reviewers through standardized tools. Bayesian NMA synthesized outcomes, including rejection, graft/overall survival, and infection rates.ResultsSixty-eight RCTs (9,626 patients) evaluating 12 therapies were included. Surface Under the Cumulative Ranking Area (SUCRA) probabilities identified alemtuzumab as the most effective agent for reducing rejection rates (93.9%), followed by antilymphocyte globulin (ALG, 87.0%) and belimumab (77.0%). For graft survival, OKT3 ranked highest (87.9%), with subsequent superiority for ALG (83.5%) and alemtuzumab (75.6%). Basiliximab demonstrated the highest overall survival benefit (88.0%), outperforming rabbit antithymocyte globulin (rATG, 82.1%) and inolimomab (70.3%). Belimumab showed the greatest infection risk reduction (94.4%), surpassing alemtuzumab (80.0%) and basiliximab (74.5%).ConclusionAlemtuzumab emerged as the optimal therapy for minimizing rejection, while OKT3 and basiliximab were superior for graft and overall survival, respectively. Belimumab exhibited the strongest potential for reducing incidence of infection. These findings highlight therapy-specific advantages for optimizing SOT outcomes.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/myprospero, identifier CRD42025634120.